2014
DOI: 10.1103/physrevb.89.125418
|View full text |Cite
|
Sign up to set email alerts
|

Creating in-plane pseudomagnetic fields in excess of 1000 T by misoriented stacking in a graphene bilayer

Abstract: It is well established that some kinds of lattice deformations in graphene monolayer

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…This similarity may support the interpretation of the twisted interlayer interaction as a non-abelian gauge field, the exact nature of which is still being investigated 26,32,36,37 . These calculations allow a very robust determination of the monolayer's Fermi velocity without a band-structure calculation, using the low-energy model for the LL's 28 :…”
Section: Bilayer Graphenementioning
confidence: 58%
“…This similarity may support the interpretation of the twisted interlayer interaction as a non-abelian gauge field, the exact nature of which is still being investigated 26,32,36,37 . These calculations allow a very robust determination of the monolayer's Fermi velocity without a band-structure calculation, using the low-energy model for the LL's 28 :…”
Section: Bilayer Graphenementioning
confidence: 58%
“…For the latter, it introduces a stackingmisorientation structure, that is, twisted graphene, forming Moiré superlattices [142]. In both cases, the electronic properties of the graphene layers can be modified dramatically and depend sensitively on the stacking orders [46,[143][144][145]. In this section, we present the characteristic features of the stacking-dependent LL spectrum in graphene bilayers and trilayers.…”
Section: Stacking-dependent Ll Spectrum For Multilayer Graphenementioning
confidence: 99%
“…(1) (in calculating B S , we use v e F = (1.250 ± 0.007) × 10 6 m/s, which was measured in our experiment). ) (here, a is on the order of the C-C bond length, and 2 < β = −∂ ln t/∂ ln a < 3) [145,216,225]. Obviously, not all the strained graphene structures result in a non-zero pseudo-magnetic field [226,227], and it is difficult to generate a uniform pseudo-magnetic field in large-area graphene [216,225].…”
Section: Valley-polarized Llsmentioning
confidence: 99%
“…In Bernal stacking, the charge carriers of the graphene bilayer have a parabolic energy spectrum and exhibit chirality that resembles those associated with spin 1. However, a twist between the two layers splits the parabolic band touching into two Dirac cones [13][14][15][16][19][20][21][22][23][24] and changes the chirality of the low-energy quasiparticles to those of spin 1/2 [18,25]. This provides a facile route to tune the electronic properties of graphene bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…These crystals engineered with one-atomic-plane accuracy provide unprecedented opportunities to explore unusual properties and new phenomena [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. It was demonstrated that properties of the van der Waals structures depend not only on their building blocks with layer-specific attributes, but also on how the 2D atomic crystals are stacked [12,[16][17][18][19]. A remarkable van der Waals crystal revealing stacking-sensitive properties is graphene bilayer.…”
Section: Introductionmentioning
confidence: 99%